Characterizing healthcare incidents in Sweden related to health information technology affecting care management of multiple patients. (30th June 2022) - Rahman Jabin, Md Shafiqur; Pan, Ding; Nilsson, Evalill
This study aimed to examine health information technology-related incidents and identify risks associated with multiple patients' management. Sources of information comprised interviews with healthcare professionals and three small sets of local voluntary incident reports using two sampling strategies, purposive and snowball sampling. Incident reports, in the form of free-text narratives, were aggregated for analysis using the Health Information Technology Classification System and thematic analysis. Of 95 incidents, 176 issues were identified, comprising 77% ( n = 136) technical issues, and 23% ( n = 40) use or human-related issues. Human issues were over two times more likely to harm patients (OR 2.25, 95% CI 1.01 - 4.98) than technical issues. Incidents that affected multiple patients' care accounted for 70% ( n = 66) of the total sample, and large-scale events comprised 39% ( n = 26) of the incidents that affected multiple patients' care. Systematically identifying and characterizing such incidents should be prioritized for health information technology implementations.